Growth Factors in Regeneration and Regenerative Medicine: “the Cure and the Cause” - Kulebyakin, Konstantin Yu.; Nimiritsky, Peter P.; Makarevich, Pavel I. (Frontiers in Endocrinology, 2020)
Potential rapid advance of regenerative medicine was obstructed by findings that stimulation of human body regeneration is definitely a tougher mission than expected after first cultures of stem and progenitor cells were established. In this mini-review we focus on the ambiguous role of growth factors in regeneration, discuss their evolutionary importance and highlight them as the "cure and the cause" for successful or failed attempts to drive human body regeneration. We draw reader’s attention to evolutionary changes that occurred in growth factors and their receptor tyrosine kinases (RTKs) and how they established and shaped response to injury in metazoan. Discussing well-known pleiotropy of growth factors we propose an evolutionary rationale for their functioning this specific way and focus on growth factors and RTKs as an amazing system that defines multicellular nature of animals and highlight their participation in regeneration. We pinpoint potential bottlenecks of their application for human tissue regeneration and show their role in fibrosis/regeneration balance. This communication invites the reader to reevaluate functions of growth factors as keepers of natively existing communications between elements of tissue which makes them a fundamental component of successful regenerative strategy. Eventually we draw attention to epigenetic landscape that may facilitate or block regeneration and make a brief insight on how it may define outcome of injury.